Documenting business-to-consumer (B2C) communications on Facebook: What have changed among restaurants and consumers?. (8th June 2015) - Kwok (Lingzhi Guo), Linchi; Zhang, Feifei; Huang, Yung-Kuei; Yu, Bei; Maharabhushanam, Prabhukrishna; Rangan, Kasturi
Abstract : Purpose: – The purpose of this study is to document how restaurant's business-to-consumer communication strategies evolved on Facebook over time and how consumers' reactions to a variety of Facebook messages changed over time. Design/methodology/approach: – This study analyzed 2, 463 Facebook messages posted by seven quick-service restaurant chains and three casual-dining restaurant chains in the fourth quarter of 2010, 2012 and 2014. ANOVA and post hoc t -test were used to compare the differences among four media types (photo, status update, video and hyperlink) in terms of their usage by companies and Facebook users' reactions to these messages (measured by number of "Likes", number of comments and number of shares). Findings: – Over the three periods of time under observation, there is a substantial decrease of status updates by restaurants and a dramatic increase of photo updates. Photo remained as the most "popular" media type, receiving most "Likes", comments and shares from consumers. Video was not considered "popular" in 2010 but experienced a slight increase in usage and slowly emerged in 2012 and 2014 as another "popular" media, which no longer had statistical difference with photo in number of comments and shares. Research limitations/implications: – Some limitations include an under representable sample and its longitudinal design, but the findings provide additional insight to current literature in social media. Practical implications: – A series of suggestions were advanced from the findings to help hospitality managers better engage Facebook users. Originality/value: – This is probably the first time-series or longitudinal-like analysis in social media research and yields meaningful findings.